2018
DOI: 10.2147/ndt.s167608
|View full text |Cite
|
Sign up to set email alerts
|

Agomelatine versus fluoxetine in glycemic control and treating depressive and anxiety symptoms in type 2 diabetes mellitus subjects: a single-blind randomized controlled trial

Abstract: BackgroundDepressive and anxiety symptoms could seriously affect the quality of life of type 2 diabetes mellitus (T2DM) subjects. Currently, little is known about the efficacy and acceptability of agomelatine versus fluoxetine in treating these symptoms in T2DM subjects. Therefore, this study was performed to find out which one was better in treating these symptoms in T2DM subjects.Materials and methodsT2DM subjects with depressive and anxiety symptoms were randomly assigned to receive either fluoxetine (30–40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Depression can conduct to a worse diabetes control, lower adoption to treatment, and increased economic burden of health care costs, besides depressive symptoms could seriously affect the quality of life of T2DM subject [6]. One study indicated that individuals with depressive symptoms are three times more likely to exhibit decreased adherence [7].…”
mentioning
confidence: 99%
“…Depression can conduct to a worse diabetes control, lower adoption to treatment, and increased economic burden of health care costs, besides depressive symptoms could seriously affect the quality of life of T2DM subject [6]. One study indicated that individuals with depressive symptoms are three times more likely to exhibit decreased adherence [7].…”
mentioning
confidence: 99%
“…One RCT (Guo et al., 2014) found that metformin improved glycemic control but also depressive outcomes, compared to placebo, in patients with type 2 diabetes. Although a small study with only 58 participants, this finding is of interest and may contribute to the expanding field of evaluation of medicines that are normally prescribed for physical conditions for their effect in treatment of depression (Arteaga‐Henríquez et al., 2019; Che et al., 2018; Köhler et al., 2014). Further research could explore the mechanism for metformin in improvement of depression in diabetes.…”
Section: Discussionmentioning
confidence: 93%
“…The repeated-measures ANOVA was conducted to explore the group differences on DHI, HDRS, and HARS scores at four time points (at baseline and at weeks 1, 2, and 4). 27 The criterion for statistical significance was set at P <0.05, and all analyses were conducted using SPSS 19.0 (IBM Corporation, Armonk, NY, USA).…”
Section: Methodsmentioning
confidence: 99%